Hacking Health How to Make Money and Save Lives in the HealthTech World - Putrino, David (Springer International Publishing, 2018)
Documents the roles and career priorities of key members of a typical HealthTech team in order to improve understanding of each team member's role; Discusses common pitfalls of HealthTech startups, including a detailed section on the regulatory processes surrounding healthcare; Examines the complex relationship between technology, entrepreneurship, and academia that are interwoven in any HealthTech venture. This book is a must-read guide for those entering the world of HealthTech startups. Author David Putrino, a veteran in the world of HealthTech and Telemedicine, details the roles, necessity, and values of key members of a typical HealthTech team, and helps readers understand the motivations and core priorities of all people involved. In ventures that typically depend upon effective communication between members from business, science, regulatory, and academic backgrounds, this book helps develop the core competencies that team members need to work harmoniously. Four detailed case studies are shared that exemplify the spectrum of HealthTech possibilities, including large corporations, tiny startups, elite athletes, and social good enterprises. Each case study shows how the success or failure of a project can hinge upon strong team dynamics, a deep understanding of the target population's needs and a strong awareness of each team member's long-term goals. This book is essential reading for entrepreneurs, scientists, clinicians, marketing and sales professionals, and all those looking to create new and previously unimagined possibilities for improving the lives of people everywhere.